KESESUAIAN KONTEN SIKLUS PENDAPATAN E-COMMERCE DENGAN MODEL END USER COMPUTING SATISFACITON (EUCS) - Yusliana, Yusliana; AR, Mulyadi (Jurnal Bisnis Digital, 2021)
This study aims to obtain empirical evidence on the suitability of e-commerce revenue cycle content using thee-user computing satisfaction (EUCS) model. The EUCS model was developed by Doll and Torkzadeh in 1987. This research is quantitative with questionnaire survey method to obtain data. The research data and hypotheses are described using the Partial Least Square (PLS) statistical tool. Respondents to this study were 79 students of accounting program, Faculty of Economics, Muhammadiyah University of Aceh. The test results show that in contsruk a user's content is calculated by application content, accuracy, format, user convenience, and punctuality according to the needs of the end user of e-commerces